Treatment results of 165 pediatric patients with non-metastatic nasopharyngeal carcinoma: A Rare Cancer Network study - (:unkn) unknown (ELSEVIER IRELAND LTD, 2006)
Purpose: This Rare Cancer Network (RCN) study was performed in pediatric nasopharyngeal carcinoma (PNPC) patients to evaluate the optimal dose of radiotherapy and to determine prognostic factors. Patients and Methods: The study included 165 patients with the diagnosis of PNPC treated between 1978 and 2003. The median age was 14 years. There were 3 (1.8%) patients with stage I, 1 (0.6%) with IIA, 10 (6.1%) with IIB, 60 (36.4%) with III, 44 (26.7%) with IVA, and 47 (29%) with IVB disease. While 21 (12.7%) patients were treated with radiotherapy (RT) alone, 144 (87.3%) received chemotherapy and RT. The median follow-up time was 48 months. Results: The actuarial 5-year overall survival (OS) was 77.4% (95% CI: 70.06-84.72), whereas the actuarial 5-year disease-free survival (DFS) rate was 68.8% (95% CI: 61.33-76.31). In multivariate analysis, unfavorable factors were age > 14 years for LRC (p = 0.04); mate gender for DMFS (p = 0.03); T3/T4 disease for LRFS (p = 0.01); and N3 disease for DFS (p = 0.002) and OS (p = 0.002); EBRT dose of less than 66 Gy for LRFS (p = 0.02) and LRRFS (p = 0.0028); and patients treated with RT alone for LRFS (p = 0.0001), LRRFS (p = 0.007) and DFS (p = 0.02). Conclusion: Our results support the current practice of using combined radiation and chemotherapy for optimal treatment of NPC. However, research should be encouraged in an attempt to reduce the potential for long-term sequelae in pediatric patients given their relatively favorable prognosis and potential for longevity. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: nasopharynx cancer; radiotherapy; pediatric; rare; 2 AGE-GROUPS; CHEMOTHERAPY; CHILDHOOD; CHILDREN; RADIOTHERAPY; ADOLESCENCE; YOUNG; EXPERIENCE; CISPLATIN